EFFECT OF COMPOST DOSES ON SOIL RESILIENCE IN PALU VALLEY - Danang Widjajanto; Uswah Hasanah; Imam Wahyudi; St Sukmawati; Sufyan Sufyan (AGROLAND The Agricultural Sciences Journal (e-Journal), 2020)
Applying organic matter to the soil surface is an effective effort to increase soil resilience in the Palu valley, which is classified as low. This study aimed to determine: 1) the effect of several doses of compost on the physico-chemical properties of the soil, 2) the correlation between the percentage of organic carbon and total nitrogen in the soil to several physico-chemical properties of the soil. The research was based on a randomized block design in a greenhouse of the Faculty of Agriculture, Tadulako University, Palu. Compost uses raw materials for plantain stems (Musa textilia) and leaves of Gamal (Gliricidia sepium). The compost doses used in the experiment consisted of 0%, 1%, 2%, 3%, 4%, and 5% of the weight of air-dry soil, respectively. The treatment was repeated three times. The results showed that compost application significantly affected soil content weight, total porosity, saturated hydraulic conductivity, field capacity moisture content, percentage of organic carbon, total nitrogen, and cation exchange capacity. The correlation test results showed a powerful relationship between the percentage of organic carbon or total soil nitrogen to other soil physico-chemical properties observed in the experiment.